Tips and Tricks and Clinical Outcome of Cryopreserved Human Amniotic Membrane Application for the Management of Medication-Related Osteonecrosis of the Jaw (MRONJ): A Pilot Study - Odet, Stéphane; Meyer, Christophe; Gaudet, Camille; Weber, Elise; Quenot, Julie; Derruau, Stéphane; Laurence, Sebastien; Bompy, Lisa; Girodon, Marine; Chatelain, Brice; Mauprivez, Cédric; Brenet, Esteban; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Medication-related osteonecrosis of the jaw (MRONJ) is a complication of certain pharmacological treatments such as Bisphosphonates, Denosumab, and angiogenesis inhibitors. There are currently no guidelines on its management, particularly in advanced stages. Human amniotic membrane (hAM) has low immunogenicity and exerts anti-inflammatory, antifibrotic, antimicrobial, antiviral, and analgesic effects. It is a source of stem cells and growth factors promoting tissue regeneration. hAM acts as an anatomical barrier with suitable mechanical properties (permeability, stability, elasticity, flexibility, resorbability) to prevent the proliferation of fibrous tissue and promote early neovascularization at the surgical site. In oral surgery, hAM stimulates healing and facilitates the proliferation and differentiation of epithelial cells in the oral mucosa and therefore its regeneration. We proposed using cryopreserved hAM to eight patients suffering from cancer (11 lesions) with stage 2 to 3 MRONJ on a compassionate use basis. A collagen sponge was added in some cases to facilitate hAM grafting. One or three hAM were applied and one patient had a reapplication. Three patients had complete closure of the surgical site with proper epithelialization at 2 weeks, and two of them maintained it until the last follow-up. At 1-week post-surgery, three patients had partial wound dehiscence with partial healing 3 months later and two patients had complete wound dehiscence. hAM reapplication led to complete healing. All patients remained asymptomatic with excellent immediate significant pain relief, no infections and a true positive impact in the patients’ quality of life. No adverse events occurred. At 6 months of follow-up: 80% of lesions had complete or partial wound healing (30% and 50% respectively), while 62.5% of patients were in stage 3. Radiological evaluations found that 85.7% of patients had stable bone lesions (n=5) or new bone formation (n=1). One patient had worsening of MRONJ but remained asymptomatic. One patient did not attend to his follow-up radiological examination. For the first time, this prospective pilot study extensively illustrates both the handling and surgical application of hAM in MRONJ, its possible association with a collagen sponge scaffold, its outcome at the site, the application of multiple hAM patches at the same time and its reapplication.